2009
DOI: 10.1002/cphc.200900606
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Large Organic Molecules on Clean and Hydroxylated Rutile TiO2(110) Surfaces

Abstract: Behavior of large organic molecules equipped with spacer groups (Violet Landers, VL) on the TiO(2)(110)-(1x1) surfaces is investigated by means of high-resolution scanning tunneling microscopy (STM). Two distinct adsorption geometries are observed. We demonstrate that the molecule adsorption morphology can be alternated by well-controlled STM tip-induced manipulation. It is used to probe the mobility of molecules and reveals locking in one of the analyzed adsorption sites, thus allow to enhance or reduce the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Godlewski et al investigated Violet Lander molecules that belong to the family of large non-planar species that are specially designed to act as molecular wires supported with spacer groups to increase the altitude of the polyaromatic board above the surface [45,64]. The authors investigated the adsorption on the (110) and (011) surfaces and observed that the molecules adsorb as single entities and adapt their conformation to the geometrical structure of the surface.…”
Section: Other Large Non-planar Moleculesmentioning
confidence: 99%
“…Godlewski et al investigated Violet Lander molecules that belong to the family of large non-planar species that are specially designed to act as molecular wires supported with spacer groups to increase the altitude of the polyaromatic board above the surface [45,64]. The authors investigated the adsorption on the (110) and (011) surfaces and observed that the molecules adsorb as single entities and adapt their conformation to the geometrical structure of the surface.…”
Section: Other Large Non-planar Moleculesmentioning
confidence: 99%
“…Increasing the distance between the active part and substrate should result in attenuated coupling between the device and the surface. Molecules with such spacer groups (often called legs) have already been examined on several substrates, for example, Lander molecules have been deposited on Cu 41, 42, TiO 2 43, 44, and InSb 45. Lander family molecules possess legs that are connected to the active board by σ bonds and are partially free to rotate.…”
Section: The Device Reliabilitymentioning
confidence: 99%
“…It has also been observed that these molecules can be manipulated by the STM tip in the “walk‐like” manner with spacer groups acting as moving legs (see, e.g., Refs. 41–44) or may create hydrogen bonds between each other leading to formation of molecular wires 46.…”
Section: The Device Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations